Construction of a high precision microscope stage and its application to the interaction of 6.2 BeV. protons with emulsion nuclei. - Ancsin, John. (University of Ottawa (Canada), 1960)
In the first part of this work the construction of a high precision microscope stage is described with particular reference to a compensating system using two pulleys. The noise measurement of this stage is made by means of an electronic system which measures noise down to a few Angstrom units. The second part is a study of the stars produced by the interaction of 6.2 Bev. protons with emulsion nuclei. The angular distribution of the pions is found in the laboratory system after reconsidering the definition of the shower particles. The results obtained indicate that in the collision of 6.2 Bev. protons with complex nuclei 3 or 4 nucleons of the target nucleus are directly involved in the pion production. The charged pion multiplicity is found to be 2.5 +/- .2 per star. These results are in agreement with those predicted by the tunnel theories.
Keywords: Physics, Nuclear.